Efektivitas City Branding Harmoni Kediri : The Service City Dalam Meningkatkan Pendapatan Asli Daerah Kota Kediri - Risdiana Himmati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Kediri Harmony: The Service City as a new brand for the City of Kediri must be able to describe the potentials in the City of Kediri. This research was conducted to find out the Kediri City Government's strategy to build regional identity in City Branding Harmony Kediri: Kediri Service city and to find out the Effectiveness of City Branding Harmony Kediri: Kediri Service city in increasing the Local Revenue of Kediri City. The method used in this study is a mix method with a sequential exploratory design. Based on research, it can be seen that City Branding Harmony of Kediri: Kediri Service City helps the City of Kediri gain a good reputation so that it becomes one of the cities of choice for large investors to invest.